GEL ELECTROPHORETIC STUDIES OF SOME BLOOD PROTEINS IN THE INDIAN SPINY-EELS (MASTACEMBELIDAE : PISCES) - KHUDA-BUKHSH, A. R.; SAHOO, P. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Electrophoretic analysis was made on three blood protein systems-plasma, haemoglobin and transferrin-in the three species of spiny-eels occurring in India, namely, Mastacembelus armatus, M. pancalus and Macrognathus aculeatum. The data demonstrated species-specific differences in all the protein systems. All the three species exhibited multiple haemoglobins which could be used as markers in species differentiation as well as for characterization of the family.